Pengetahuan dan Sikap tentang Penyakit Infeksi Menular Seksual (PIMS) di Kalangan Mahasiswa - Safira, Nanda; Mohammad Fahdhy (J-Mestahat, 2023)
Sexually transmitted infections such as HIV/AIDS have increased globally, particularly in Indonesia. Young people between the ages of 16 and 24, revealed an increase in STI incidence as a result of unsafe sexual conduct. The purpose of this study was to assess the knowledge and attitudes about STIs among college students. We conducted a descriptive cross-sectional study from various semesters and faculties from June to July 2023. A questionnaire on their knowledge and attitude toward sexually transmitted infections (STIs) was done by face-to-face interview with prior consent during data collection. We assessed association between low knowledge (vs. high) and being health courses university students (vs. non-health courses) using multivariate logistic regression with adjustment for potential confounders. The study included 29 men and 83 women. Less knowledge about STIs was observed among non-health courses university students. Participants made the most mistakes when asked about Chlamydia. Most participants got their information about STIs from teachers, the internet, or friends. The students' attitudes on sexual health and STI prevention were also different. Our study's findings indicate that it is critical to educate students on sexual health and safe sexual behaviors, as this will aid in the prevention and control of STIs. Keywords: knowledge, attitudes, sexually transmitted infections, college students, Indonesia